Analysis of optimal boundary control for a three-dimensional reaction-diffusion system - Yang, W.; Sun, Jie; Zhang, S. (American Institute of Mathematical Sciences, 2017)
This paper is concerned with optimal boundary control of a three dimensional reaction-diffusion system in a more general form than what has been presented in the literature. The state equations are analyzed and the optimal control problem is investigated. Necessary and sufficient optimality conditions are derived. The model is widely applicable due to its generality. Some examples in applications are discussed.